A low cost outdoor testing facility for detailed photovoltaic device performance characterization. Issue 9 (25th September 2015) - Ogulgonen, Guvenc; Ozden, Talat; Yardim, Ugur; Turan, Rasit; Kincal, Serkan
Abstract: Long term outdoor performance monitoring is the ultimate method to capture the long term performance characteristics of PV devices. As time consuming as this process might be, it is the only way in which the local environmental condition versus PV device characteristics may be captured when making investment decisions. This data needs to be captured at least once through the seasonal cycle. It needs to be correlated to the environmental conditions, this monitoring climatic conditions is a requirement. Solar irradiation conditions must be monitored over a range of inclination angles – direct, diffuse and reflected components must be ideally captured separately. The panels must be held at maximum power generating point through the varying illumination conditions. Periodic IV traces must be captured, in addition to the power output to understand mechanisms of degradation, if present. Furthermore, the IV curves must be summarized in terms of relevant performance metrics. This work describes an outdoor testing facility that addresses all the aforementioned requirements. Reliable equipment selections coupled with adequate modelling strategies allow for the generation of a robust and accessible database of performance data. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)